2010
DOI: 10.4319/lo.2011.56.1.0243
|View full text |Cite
|
Sign up to set email alerts
|

Source, biogeochemical cycling, and fluorescence characteristics of dissolved organic matter in an agro‐urban estuary

Abstract: Seasonal measurements of dissolved organic matter (DOM) fluorescence characteristics were combined with weekly to bi-weekly measurements of carbon (C), nitrogen (N), and phosphorus (P) (including particulate, dissolved organic and inorganic forms) and chlorophyll to determine how riverine inputs and autochthonous production influence DOM and nutrient dynamics in the Swan-Canning estuary, Western Australia. Estuarine concentrations of C, N, and P were influenced by multiple factors, including the seasonal river… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
55
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(64 citation statements)
references
References 65 publications
7
55
0
Order By: Relevance
“…These methods primarily dependent on the ultraviolet-visible (UV-Vis) and fluorescence measurements have been widely applied and reported (Chin et al, 1994;Vodacek et al, 1997;Helms et al, 2008;Zhang et al, 2007Zhang et al, , 2010Fellman et al, 2011;Stedmon et al, 2011). Using the ratio of the absorptions at 250 to 365 nm (E 250 : 365 ), De Han and De Boer (1987) successfully tracked changes in DOM molecule size, which was confirmed by other researchers (Peuravouri and Pihlaja, 1997;Zhang et al, 2007).…”
Section: Introductionmentioning
confidence: 50%
See 2 more Smart Citations
“…These methods primarily dependent on the ultraviolet-visible (UV-Vis) and fluorescence measurements have been widely applied and reported (Chin et al, 1994;Vodacek et al, 1997;Helms et al, 2008;Zhang et al, 2007Zhang et al, , 2010Fellman et al, 2011;Stedmon et al, 2011). Using the ratio of the absorptions at 250 to 365 nm (E 250 : 365 ), De Han and De Boer (1987) successfully tracked changes in DOM molecule size, which was confirmed by other researchers (Peuravouri and Pihlaja, 1997;Zhang et al, 2007).…”
Section: Introductionmentioning
confidence: 50%
“…High values of both E 250 : 365 and Sr are observed in brackish waters, which may be regulated by the DOC flux for inland waters both in time and space (Jaffé et al, 2008;Spencer et al, 2009Spencer et al, , 2012Zhang et al, 2010;Fellman et al, 2011). Nevertheless, the E 250 : 365 and Sr values are found to be useful for indicating seasonal DOC compositional variations (Fichot and Benner, 2011).…”
Section: Dissolved Organic Carbon In Fresh and Brackish Watersmentioning
confidence: 99%
See 1 more Smart Citation
“…Fellman et al, 2010;Helms et al, 2008), especially when combined to parallel factor analysis (PARAFAC, Murphy et al, 2013;Stubbins et al, 2014). Spectroscopic measurements of DOM composition revealed that DOM from catchments with intensive agriculture is usually dominated by complex, humic fluorophores, is characterized by high humification and low contribution of protein-like fluorophores, and is likely to be released from microbial sources (Wilson and Xenopoulos, 2009;Williams et al, 2010;Graeber et al, 2012b;Fellman et al, 2011;Heinz et al, 2015). Moreover, existing time series indicate a stable composition of DOM exported from agricultural catchments across seasons, most likely linked to stable catchment DOM sources (Graeber et al, 2012b;Heinz et al, 2015).…”
mentioning
confidence: 99%
“…characterized dissolved organic matter as 'humic-like' and 'protein-like' fluorophores. While the former are mainly derived from soil OM and plants, the latter may be plankton-derived and positive correlation between the 'protein-like' fluorescence and DOM bioavailability have been reported (Hood et al, 2009;Fellman et al, 2011). Therefore, 'protein-like' fluorescence has been applied as a proxy for bioavailable DOM (Fellman et al, 2009) and an indicator for biological reactivity of DOM (Parlanti, et al, 2000).…”
mentioning
confidence: 99%